A Preliminary Study on the Construction of Curriculum Ideology and Politics in College English Course - Yan, Yi (Journal of Theory and Practice of Social Science, 2024)
The purpose of this paper is to discuss the importance of the construction of curriculum ideology and politics in college English course, to explore the implementation plan of college English course on curriculum ideology and politics, and to propose the teaching idea of introducing online teaching to make up for the lack of classroom teaching time, in order to achieve the best effect of teaching and educating. Chinese is the basic subject in education, and it is also the most important subject. It is not only the precipitation of China's 5000year civilization, but also the way for students to understand the excellent connotation of ancient China. Therefore, the study of Chinese plays a key role in the inheritance of Chinese traditional culture. But in the current stage of Higher Vocational Chinese learning process, pay more attention to the teaching of Chinese knowledge points, ignoring the improvement of students' humanistic quality, which is an essential ability of students at this stage. In the current stage of Higher Vocational Chinese teaching, we need to pay attention to the improvement of students' humanistic quality, to improve students' comprehensive quality. Therefore, this paper focuses on the cultivation of students' Humanistic Quality in Higher Vocational Chinese teaching.